Supporting patients and carers affected by pancreatic cancer: A feasibility study of a counselling intervention. (June 2020) - Beesley, Vanessa L.; Turner, Jane; Chan, Raymond J.; Yates, Patsy; Gordon, Louisa G.; Burge, Matthew; Eastgate, Melissa A.; Staneva, Aleksandra A.; Northfield, Sarah; Beebe, Hanna; Wyld, David K.; Neale, Rachel E.
Abstract: Purpose: Patients with pancreatic cancer have extremely high unmet psychological and physical needs. Family carers of these patients have even higher levels of distress than patients. Our purpose was to assess the feasibility and acceptability of a counselling intervention in patients diagnosed with pancreatic cancer and their carers. Methods: We conducted a single-arm feasibility study of the PREPARES (Patients and RElatives affected by PAncreatic cancer: Referral, Education and Support) pilot intervention. Patient and carer participants received up to nine counselling sessions delivered by a trained nurse via telephone and/or telehealth technology. The intervention, informed by self-efficacy theory, involved components to assess and address care needs, and provide feedback to clinicians. Feasibility was measured using participation and retention rates. Participants completed semi-structured interviews at the end of the intervention about acceptability. These were analysed using thematic analysis. Results: Twelve people participated: five patients and seven carers (38% and 50% participation rates respectively). Most participants (eight) completed all nine counselling sessions; two chose to receive fewer sessions and two were discontinued requiring more intensive psychiatric support. The intervention was highly acceptable. Participants unanimously preferred the telephone over video-conferencing and to receive counselling separately from their carer/patient. The main perceived benefits were emotional support, the nurse-counsellors' knowledge, care coordination and personalised care. Suggested improvements included a welcome pack about their nurse-counsellor and that sessions should continue beyond nine sessions if required. Conclusions: The PREPARES intervention was feasible and highly acceptable. This low-cost intervention provided much-needed support to people affected by this devastating disease. Highlights: This intervention addressed the care needs of pancreatic cancer patients and carers. While 56% declined participation, participants said the intervention was excellent. Participants preferred the telephone delivery over video-conferencing. Perceived benefits were nurse-led emotional support and care coordination. Suggested improvements were welcome packs and more intervention sessions.